General characteristics, risk-stratified and sex-stratified clinical outcomes in Bangladeshi people with type 2 diabetes mellitus who fasted during Ramadan 2022: A multicenter, real-world, cross-sectional study (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2026)
Background: Fasting during Ramadan presents both spiritual significance and physiological challenges, particularly for individuals with type 2 diabetes mellitus (T2DM). While previous research has yielded mixed results, there remains a gap in real-world multicenter data on the clinical impact of fasting in risk- and sex-stratified patients with T2DM.Objective: The study aimed to assess the characteristics and clinical and behavioral outcomes among T2DM patients who fasted during Ramadan 2022, stratified by risk using the International Diabetes Federation-Diabetes and Ramadan (IDF-DAR) criteria 2021, and also stratified by sex.Methods: This cross-sectional, multicenter survey was conducted across 14 tertiary hospitals in Bangladesh following Ramadan 2022. Adult patients with T2DM who had fasted for at least 1 day were included and categorized into low-, moderate-, and high-risk groups using the IDF-DAR risk score (2021). Data were collected on demographics, fasting practices, hypoglycemia, glucose monitoring, and clinical parameters, including HbA1c and comorbidities.Results: Of 2,382 screened patients, 2,304 were included and categorized into low-risk (n=231; 10.0%), moderate-risk (n=660; 28.6%), and high-risk (n=1,413; 61.3%) groups according to IDF-DAR 2021 criteria. Hypoglycemia was more frequent among high-risk patients (26.9%) compared to moderate (14.5%) and low-risk (9.5%) groups. Only 53.4% of high-risk individuals received pre-Ramadan counseling, and 29.6% did not self-monitor blood glucose despite clinical indications. Females were more likely to rely on symptoms rather than glucose testing for hypoglycemia detection (64.7% vs. 44.0%; p